Design sušičky filamentu - Belevitskaia, Alina (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2025)
Práce se zabývá návrhem designu sušičky filamentu pro 3D tisk. Hlavním cílem je vytvořit esteticky i funkčně propracovaný design sušičky, který odpovídá technickým požadavkům a nárokům na bezpečnost, životnost a ergonomii. Práce kombinuje technické a designérské přístupy s cílem vyvinout uživatelsky přívětivý produkt, který zlepší efektivitu a kvalitu procesu 3D tisku.

Bachelor thesis focuses on designing a filament dryer for 3D printing. The main goal is to create an aesthetically and functionally refined design that meets technical requirements and standards for safety, durability, and ergonomics. Part of the thesis is technical and design approaches to develop a user-friendly product that enhances the efficiency and quality of the 3D printing process.
Design of Filament Dryer
Keywords: sušička filamentu; horkovzdušné sušení; dvoupolohové použití; design; filament dryer; hot air drying; dual-position use; design